BIMBINGAN BELAJAR MEMBACA AL-QUR’AN GRATIS PADA ANAK ASUH RUMAH PINTAR ACIBU DESA PURWODADI KECAMATAN PADANGSIDIMPUAN BATUNADUA - Samsidar Lubis; Muksana Pasaribu; Rosmaimuna Siregar; Rini Agustini; Jumaita Nopriani Lubis (Universitas Muhammadiyah Tapanuli Selatan, 2021)
In Islam, the Koran and Al-Hadith are two sources that serve as the basis for Muslims. In order to better understand and study the contents of the Al-Qur'an, a Muslim must have the ability to read the Al-Qur'an. For Muslims studying the Koran is obligatory because it contains Islamic teachings regarding the commandments and all the prohibitions so that humans are safe in the world and the hereafter. The Purwodadi area of Padangsidimpuan Batunadua district has a smart house called the Acibu (I Love Books). This smart house has foster children aged 9-12 years old belonging to elementary school children from a similar family in Purwodadi Village. The Acibu Smart House does not have programs related to the religious field, therefore it is necessary to provide children with the ability to read the Qur'an. Referring to this existing reality, it is very necessary to provide actions that enable participants to read the Qur'an by making free tutoring at the Acibu Purwodadi Smart House, Padangsidimpuan Batunadua District. This PKM activity is carried out only 2 times a week every Wednesday and Thursday with a limited time of only 3 hours a day, from 14.00 to 17.00